2006
DOI: 10.1536/ihj.47.745
|View full text |Cite
|
Sign up to set email alerts
|

Association of Renal Insufficiency With In-Hospital Mortality Among Japanese Patients With Acute Myocardial Infarction Undergoing Percutaneous Coronary Interventions

Abstract: SUMMARY Itis not yet clear whether a difference in in-hospital morality between patients with and without renal insufficiency undergoing percutaneous coronary intervention (PCI) exists. Therefore, the aim of the present study was to investigate if such as association exists in Japan. Data from the Tokai Acute Myocardial Infarction Study II were used. This was a prospective study of all 3274 patients admitted with acute myocardial infarction (AMI) to the 15 participating hospitals from 2001 to 2003. We abstract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…In addition to older age and female gender, RD was more frequently associated with hypertension, diabetes, higher Killip class, multivessel disease and low left ventricular ejection fraction. These findings which have been described by other authors13)19)21) predispose to worse clinical outcomes after AMI. However, after adjustment for baseline differences, increased in-hospital mortality persisted in the patients with RD, suggesting that an increased mortality in patients with RD was not fully explained by these associated conditions, and that RD is a strong independent predictor of in-hospital mortality.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition to older age and female gender, RD was more frequently associated with hypertension, diabetes, higher Killip class, multivessel disease and low left ventricular ejection fraction. These findings which have been described by other authors13)19)21) predispose to worse clinical outcomes after AMI. However, after adjustment for baseline differences, increased in-hospital mortality persisted in the patients with RD, suggesting that an increased mortality in patients with RD was not fully explained by these associated conditions, and that RD is a strong independent predictor of in-hospital mortality.…”
Section: Discussionsupporting
confidence: 77%
“…Although RD, as defined by either serum creatinine level or estimated GFR, has been associated with increased mortality in patients with AMI,13-15)18)19)21) serum creatinine level is insensitive for an early detection of RD and could underestimate the incidence of moderate or severe RD concealed behind the near-normal creatinine levels,9)22)23) thereby underscoring the risk of RD in AMI patients. Furthermore, a graded risk of RD clearly exists, RF should be classified into at least 3 groups using estimated GFR for appropriate RD risk stratification in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…RD is reported to be an independent predictor in AMI patients undergoing PCI [16, 17, 25]. Kim et al reported that the multivariable OR (95% CI) of In-HD was 2.67 (1.44 - 4.93, P = 0.002) for patients with eGFR of 30 - 59 mL/min/1.73m 2 , and 4.09 (1.48 - 11.28, P = 0.006) for those with eGFR < 30 mL/min/1.73m 2 compared to those with eGFR ≥ 60 mL/min/1.73 m 2 in AMI patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…Japanese Coronary Intervention Study Group observed risk factors of In-HD including attempted PCI to left main coronary artery (LMC) disease, LV dysfunction, LMC disease, older age, multi-vessel disease, cerebrovascular disease, and diabetes as independent predictors [6]. In addition, many predictors of In-HD were pointed in AMI patients: female sex [7-12], diabetes [13, 14], obesity [15], and renal dysfunction (RD) [16-19]. …”
Section: Introductionmentioning
confidence: 99%
“…Impaired renal function has been recognized as the determinant of in-hospital death in patients with AMI. 13,14) Since impaired renal function was associated with multiple risk factors, such as hypertension, diabetes mellitus, and smoking, 15,16) patients with AMI and impaired renal function might have advanced atherosclerosis, which was not evaluated in the present study. Furthermore, low eGFR levels in the "in-hospital death group" might be a result of malperfusion following CS.…”
Section: Discussionmentioning
confidence: 98%